Improving self-efficacy beliefs and English language proficiency through a summer intensive program. (July 2022) - Xu, Mei; Wang, Chuang; Chen, Xiangjing; Sun, Ting; Ma, Xiaomei
Abstract: This study examines the impacts of an intensive summer English training program on the self-efficacy beliefs and listening and speaking skills of college students at a large university in northwestern China. Mixed analysis of variance was employed to examine changes in students' self-efficacy beliefs and English listening and speaking skills before and after the program. Hierarchical linear regression was used to measure the extent to which self-efficacy beliefs can explain the variance of participants' listening and speaking skills after the control of covariates such as gender, track, and pretest scores for listening and speaking, respectively. Results suggest that students improved their self-efficacy beliefs after the program although the changes in listening and speaking skills were not statistically significant. Pretest listening self-efficacy predicted posttest listening skills, but pretest speaking self-efficacy did not make any contributions to the prediction of posttest speaking skills. Discussions of these findings related to the self-efficacy theory and summer training programs were presented.